Increasing Mothers' Knowledge, Attitudes, and Actions through Stunting-Based Prevention Education AECAS App - Debora Natalia Simamora; Nova Lumbantoruan; Nova Sontry Node Siregar; Mayes Felda Simamora (Jurnal EduHealth, 2023)
Babies and toddlers in Indonesia often experience stunting, with around 21.6% of them affected by this condition. In North Sumatra, the prevalence reached 21.1%, while in Humbang Hasundutan, the figure reached 29.6%. A survey in Simarigung Village found that 27 toddlers were stunted. This study aims to evaluate the benefits of stunting prevention education based on the AECAS application, with a focus on increasing the knowledge, attitudes, and actions of mothers in Simarigung Village. This research used a quasi-experimental design with pre-test and post-test, involving 47 mothers of babies and toddlers using Android cellphones. The sampling method used was total sampling, and a paired t-test was carried out to analyze the results. The research results show a difference between the pretest and posttest with a confidence level of 95%. In the knowledge variable, there was a significant increase (p-value=0.000 < 0.05) with a Mean Paired Difference of 0.34. The attitude variable also showed a significant increase (p-value=0.000 <0.05) with a Mean Paired Difference of 0.36. Likewise, the action variable showed a significant increase (p-value = 0.000 < 0.05) with a Mean Paired Difference of 0.27. The results of the normality test show that the data for the Knowledge, Attitude, and Action variables are normally distributed. Therefore, it is hoped that respondents can increase their understanding of preventing stunting in infants and toddlers thanks to the education provided through the AECAS application